Digital media investigators: challenges and opportunities in the use of digital forensics in police investigations in England and Wales. Issue 4 (7th May 2021) - Wilson-Kovacs, Dana
Abstract : Purpose: In-depth knowledge about specific national approaches to using digital evidence in investigations is scarce. A clearer insight into the organisational barriers and professional challenges experienced, alongside a more detailed picture of how digital evidence can help police investigations are required to empirically substantiate claims about how digital technologies are changing the face of criminal investigations. The paper aims to focus on the introduction of digital media investigators to support investigating officers with the collection and interpretation of digital evidence. Design/methodology/approach: Drawing on ethnographic and interview data collected as part of an Economic and Social Research Council-funded project on the application of digital forensics expertise in policing in England and Wales, this paper examines the changing face of investigations in relation to escalating digital demand. Findings: The analysis presents the national and regional organisational parameters of deploying digital expertise in criminal investigation and examines some of the challenges of being a digital media investigator (DMI). Through testimonies from DMIs, digital forensic practitioners, investigating and senior officers and forensic managers, the analysis explores the organisational tensions in the collection, processing, interpretation and use of information from digital devices for evidential purposes. Research limitations/implications: The paper offers an empirical basis for the comparative study of how the DMI role has been implemented by law enforcement agencies and its fit within broader institutional considerations and processes. Practical implications: The development of the DMI role has raised questions about the supply of digital expertise, especially to volume crime investigations, and tensions around occupational divisions between scientific and operational units. Social implications: The findings show that while the introduction of the DMI role was much needed, the development of this valuable provision within each force and the resources available require sustained and coordinated support to protect these professionals and retain their skills. Originality/value: This study contributes to the growing sociological and criminological literature with an ethnographically based perspective into the organisational and occupational tensions in the identification and processing of digital evidence in England and Wales.